Altered EEG Microstates Dynamics During Cue-Induced Methamphetamine Craving in Virtual Reality Environments - Lin, Qianqian; Li, Dongxu; Hu, Cheng; Shen, Zhihua; Wang, Yongguang (Frontiers in Psychiatry, 2022)
Background: Cue-induced craving is widely considered to be the most important risk factor for relapse during abstinence from methamphetamine (Meth). However, there is limited research regarding electroencephalogram (EEG) microstates for Meth-dependent patients during cue-induced craving. Our objective was to investigate whether EEG microstate temporal characteristics could capture neural correlates of cue-induced methamphetamine craving in virtual reality environments. Methods: EEG recording were collected during eyes-opened state and cue-induced state, and then we performed EEG microstates analysis on 35 Meth-dependent patients and 30 healthy controls to explore group differences and condition differences in the duration, coverage, occurrence, and transition probability of four microstate maps. Results: We found the greater presence of microstate B in both Meth-dependent patients and healthy controls during cue-induced condition, compared to resting state. In addition, for Meth-dependent patients, microstate C occurred significantly less frequently, along with a tendency of increased the occurrence for class D during cue-induced condition, compared to resting state. However, the change direction of class C and class D in healthy controls were completely opposite to that of Meth-dependent patients. Cue-induced condition also elicited different changes of transition probability between Meth-dependent patients and healthy controls. Conclusion: This study explored abnormal features of EEG microstates in Meth-dependent patients during cue-induced condition, which can improve our understanding of methamphetamine addiction and contribute to the development of effective assessments and intervention tools.